PERSEPSI MASYARAKAT TERHADAP PEMBANGUNAN JEMBATAN SEI BINGEI - Heny Sri Dewi Sitepu; Heri Kusmanto; Muryanto Amin (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2020)
Facilities and infrastructure as an important instrument in the effort to do development on multi aspects of life. This study aims to see the public perception of the construction of the bridge Sei Bingei Village Berngam District Binjai Binjai Towns. Data collection techniques used in this study are in-depth interviews, observation, literature study and documentation. The result of the research shows that the construction of the sei bingei bridge is not followed by the improvement of the completeness of the public transportation infrastructure so that the existence of the Sei Bingei Bridge can not be utilized optimally for the mobilization rate of social life and the economy of the community.